Endangered species interactions suggest a role for personality and behavioral syndromes in conservation efforts. Issue 1 (2nd January 2017) - Snekser, J.L.; Wynne, R.D.; Itzkowitz, M.
Abstract : Conservation efforts should consider many aspects of the endangered species' life history and behavioral ecology. Additionally, when multiple endangered species interact, those relationships must also be considered when exploring recovery plans for either or both species. In our continued efforts to conserve the critically endangered Leon Springs pupfish ( Cyprinodon bovinus ), we explored consistency in aggression toward the endangered sympatric Pecos gambusia ( Gambusia nobilis ), that attempt to prey upon pupfish eggs during spawnings. We repeatedly observed 13 territorial male pupfish and measured individual aggression, focusing on defensive chases against gambusia and interactions with other pupfish. Short-distance chases at gambusia and chases of territorial neighbors were significantly repeatable, indicating that pupfish show behavioral consistency, or "personality". Moreover, male pupfish that gave more short chases to gambusia experienced higher spawning success. Together, these data suggest that personality can predict reproductive success and thus should be considered by managers working to conserve endangered populations. Conservationists should take into consideration that differential reproductive success may certainly be relevant to the recovery of at-risk species.